Ellenberg N values of bryophytes in Central Europe*. (18th October 2020) - Simmel, Josef; Ahrens, Matthias; Poschlod, Peter
Abstract: We present a list of Ellenberg indicator values N values for Central European bryophytes and the methodology we used to obtain these values. Values are given for 6 hornworts, 255 liverworts, 35 peat mosses, and 772 mosses, i.e., for a total of 1, 068 species. We ng the N values for different variables related to bryophyte morphology, taxonomy, Red List status, and ecology. Among the morphological and taxonomical groups, peat mosses, foliose hepatics, and species with porous leaves on average had the lowest N values, while no strong differentiation was found between Red List groups. Ecology and life span exhibited a strong differentiation, with lowest mean values for aquatic and indefinitely growing species, and highest mean values for ecologically rather unspecific and annual species. Furthermore, we compared the bryophyte N values with those of vascular plants and macromycetes from Central Europe. Abstract : List of Ellenberg indicator values N values for 1, 068 Central European bryophytes. Analyses regarding morphology, taxonomy, Red List status, ecology. Lowest N values for peat mosses, foliose hepatics, species with porous leaves. Strong differentiation for ecology, life span. Comparison of bryophyte N values with vascular plants, macromycetes.